2018
DOI: 10.1111/jan.13575
|View full text |Cite
|
Sign up to set email alerts
|

Associations of eHealth literacy with health‐promoting behaviours among hospital nurses: A descriptive cross‐sectional study

Abstract: Improving eHealth literacy through various strategies could be an effective way to boost health-promoting behaviours among nurses. However, improvement of actual health-promoting behaviours such as nutrition and physical activity will require systematic and organizational changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 32 publications
2
65
0
Order By: Relevance
“…The information literacy of nurses can help them effectively obtain valuable information in clinical nursing work and make correct information decision timely, which is closely related to the quality of clinical nursing service [20,21]. Studies have found that good information literacy of nurses is conducive to promoting the health of patients [22,23]. Therefore, it is necessary and meaningful to make clear the status of nurses' information literacy, nd out the in uencing factors, and give targeted guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The information literacy of nurses can help them effectively obtain valuable information in clinical nursing work and make correct information decision timely, which is closely related to the quality of clinical nursing service [20,21]. Studies have found that good information literacy of nurses is conducive to promoting the health of patients [22,23]. Therefore, it is necessary and meaningful to make clear the status of nurses' information literacy, nd out the in uencing factors, and give targeted guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy is an essential issue to consider in the programmes planned for decreasing the inequalities and increasing the health selfresponsibility in disadvantaged groups for health promotion (Mahamed, Parhizkar, & Shirazi, 2012;Mahdizadeh & Solhi, 2018;Mas et al, 2015). Women are a disadvantaged group, who yet play a key role in protecting and promoting the health of both their society and their family (Cho, Han, & Park, 2018;Komenaka et al, 2015;Messadi et al, 2018;Wang, Lin, Yang, Tsai, & Huang, 2012). Therefore, it is vital to increase the health literacy levels of women.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO (2012) emphasizes the importance of increasing health literacy levels in its health promotion programmes based on empowering individuals and increasing community participation. In the literature, it is reported that the health literacy level of women is related to developing healthy life style habits and positive health behaviours (Cho et al, 2018;Mahamed et al, 2012;Mahdizadeh & Solhi, 2018;Plummer & Chalmers, 2017). It is accepted that "adequate" health literacy for women is a significant indicator of the health-promoting behaviours such as healthy eating, normal body mass index, quitting smoking and alcohol drinking, regular physical activity, and regular medical screening (Knobf, Erdos, & Jeon, 2018;Komenaka et al, 2015;Plummer & Chalmers, 2017;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, among nurses, those with higher levels of eHealth literacy had significantly more positive health-promoting behaviours related to stress management, interpersonal relationships, self-actualization, and health responsibility (Cho, Han, & Park, 2018).…”
Section: Introductionmentioning
confidence: 92%